ANALYSIS OF CULTURAL ASPECTS IN THE GERMAN TRANSLATION OF THE POLISH PENAL CODE - SIEWERT, Katarzyna (Comparative Legilinguistics, 2014)
Translation of legal texts is a specific kind of cultural transfer because law and its language are an integral part of social culture. They are not only a result of a centuries-old historical evolution but also a reflection of a specific vision and understanding of the reality which is organised by the particular society through legal institutions. The translator is, therefore, expected to have not only specialist knowledge but also cultural competence which enables him to identify cultural elements in the source text and to reconstruct them in the target text. The present article intends to analyse selected examples from the newest German translation of the Polish penal code, focusing on translation solutions on different levels of the text in order to reconstruct cultural dissimilarity.